Optical Coherence Tomography with Angiography in the Diagnosis of Changes in the Organ of Vision at Atherosclerosis - M. S. Kasimova; D. K. Mahkamova (Oftalʹmologiâ)
Background. The study of the parameters of optical coherence tomography with angiography (OCTA) broadens the understanding of the state of hemodynamics for the early detection of vascular disorders of the organ of vision in atherosclerosis (AS).Purpose. To study the parameters of OCTA with changes in the organ of vision against the background of AS.Patients and methods. 26 patients (41 eyes) with changes in the organ of vision in AS. The age contingent of patients ranged from 32 to 78 years, the average age was 47.5 ± 2.0 year, of which 10 were women, 16 men. Depending on the damage to target organs, all patients were conditionally divided into 2 groups: group I (19 eyes) included patients without damage, and group II (22 eyes) consisted of patients with target organs damage.Results. The registration of OCTA in patients of group I, a decrease in the density of capillaries of the superficial vascular network was 15 % and amounted to 45.21 ± 2.62 % (p < 0.05), of the deep vascular plexus by 19 %, which amounted to 45.89 ± 2, 71 % (p < 0.05). In the macular region, the area of the hypoperfused retina was 1.07 ± 0.14 mm2 (p < 0.05). In the region of the optic nerve disc, areas of hypoperfusion were noted in the superficial layers in 7 eyes and in the deep layers in 4 eyes. Analysis of OCTA in patients of group II revealed a sharp decrease (by 48 %) in the density of capillaries in both the superficial and deep vascular plexuses of the retina, which amounted to 33.91 ± 3.01 % (p < 0.05); 33.65 ± 2.89 % (p < 0.05), respectively. In the macular region, the area of the non-perfused retina was 2.19 ± 0.21 mm2 (p < 0.05). In the area of the optic nerve disc, areas of nonperfusion were noted both in the surface layers and in the deep layers in 4 eyes.Conclusion. The use of OCTA allows to detect changes in hemoperfusion in all layers of the retina and optic nerve in the early stages of AS development, which will allow early diagnosis and monitoring of the disease.